2021
DOI: 10.3390/jcm10081759
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Geographic Disparities in the Mortality Rates of Primary Systemic Vasculitis in the United States from 1999 to 2019: A Population-Based Study

Abstract: The current data on rates and geographic distribution of vasculitis mortality are limited. We aimed to estimate the mortality rates of primary systemic vasculitis and its geographic distribution using recent population data in the United States. The mortality rates of vasculitis from 1999 to 2019 were obtained from the Center for Disease Control (CDC) Wonder Multiple Cause of Death (MCD). The age-adjusted rates per million for vasculitis as MCD and as an underlying cause of death (UCD) were calculated by state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Before corticosteroids and cytotoxic agents were used for granulomatosis with polyangiitis, the one-year mortality rate was between 50% and 80%. Once combination therapy with cyclophosphamide, azathioprine, and steroids became popular in the 1970s, ANCA-associated vasculitis achieved an 80-90% survival rate [ 9 ]. Thus, early diagnosis and treatment of ANCA-associated vasculitides is critical for lengthening survival for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Before corticosteroids and cytotoxic agents were used for granulomatosis with polyangiitis, the one-year mortality rate was between 50% and 80%. Once combination therapy with cyclophosphamide, azathioprine, and steroids became popular in the 1970s, ANCA-associated vasculitis achieved an 80-90% survival rate [ 9 ]. Thus, early diagnosis and treatment of ANCA-associated vasculitides is critical for lengthening survival for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that GCA is the second leading cause of death in primary vasculitides in the US [ 22 ]. Nonetheless, the risk of GCA-related death stays lower as <1% of GCA hospitalized patients died in-hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In the published papers about EGPA, patients were almost from the cohort of the French Vasculitis Study Group or the United States (7,8,(14)(15)(16)(17)(18)(19), and comprehensive data from Asia, especially from China, were scarce. Therefore, we established such an EGPA cohort to provide more information from China in the field of EGPA.…”
Section: Discussionmentioning
confidence: 99%
“…The French Vasculitis Study Group published their findings 20 years ago (14) and subsequently updated many contents from the same cohort in 2013 and 2021 (8,17), which may be because the disease process and outcomes have been changed with the development of EGPA diagnosis and treatment. For instance, one study from Rodriguez-Pla et al revealed that, since 1999, the mortality rates of patients with primary systemic vasculitis have progressively decreased in the United States, and they demonstrated the mortality trends of vasculitis in gender, racial, and geographic disparities (19). Therefore, studies from different regions, races, and year ranges are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation